JUDICIAL OFFICERS' KNOWLEDGE OF PSYCHOLOGY AND ITS PERCEIVED IMPACT ON EFFECTIVE JUSTICE ADMINISTRATION IN NASARAWA STATE - Ruwan, Ibrahim Ignatius Felix; Iliya, Vakpa; Okorie, Agnes O; Fadare, Gbenga Oba; Jose, Charlton (African Journal of Social and Behavioural Sciences, 2020)
This paper examined Judicial Officers' knowledge of Psychology and its perceived impact on effective Justice Administration. Using Survey paper method, 49 participants comprising of 42 Lawyers and 7 Magistrates within Karu and Keffi LGA of Nasarawa State participated in the study. Structured questionnaires were used to collect the data. Three research hypotheses were tested. The study found that: i). There was a relationship between Judicial Officers Knowledge of Psychology and Perceived effective justice administration. ii) There was no significant difference between lawyers and magistrates on their knowledge of psychology. iii) But there was a significant difference between junior lawyers and senior lawyers on the perceived impact of psychology knowledge on effective justice administration. Discussion, conclusion and recommendations were made which include the need for a synergy between the two professional regulatory bodies that is the Nigeria Psychological Association and Nigeria Bar Association to facilitate mutual professional co-operation. Psychologists should diversify their interest towards enhancing effective justice administration and the justice system entirely.